Cooperative Farming dalam Kebijakan Pemberdayaan Petani di Provinsi Bali - I Made Mahadi Sanatana (Jurnal Ilmiah Cakrawarti, 2020)
Poverty is found in the majority of people whose inhabitants work in  the agricultural sector. The government has made some policy to improve the per- formance of farmers, both those that are on farm and programs that include added value to off-farm. But the results remain inefficient and ineffective. The main prob- lem of all that is the weakness of the farm management system, which is still done individually. The implication of the individualist management system for small- holders is the difficulty of moving from subsistence. In real terms they remain in a weak condition (powerless) in everything. As in land tenure, information, capital provision, procurement of agricultural production facilities, procurement of labor, marketing, processing, and so on. The problem of agricultural development is not the technological device, but the institutional structure in rural communities, which determines whether the technology has a negative or positive impact on income dis- tribution, institutional aspects will continue to play an important role in agricultural development, so a special effort to empower farmers is needed, among others done through cooperative farming.